Youtube Implementation in Teaching English as a Foreign Language: A Review - Setiawan, Rama; Novita, Dian (Indonesian Journal Publisher, 2024)
As social media becomes increasingly woven into people lives, educators are exploring its impact on learning, particularly in English as a Foreign Language (EFL). This study investigates the effectiveness of YouTube, a platform brimming with engaging educational content in EFL classrooms. Through qualitative research and analysis of existing studies, the research confirms YouTube's potential. Students not only experience improved proficiency in various skills like vocabulary, grammar, and listening, but also increased interest, motivation, and autonomy in their learning journey. For teachers, YouTube offers a treasure trove of diverse content, enabling them to create captivating instructional materials and enhance the overall teaching process. Ultimately, this study reveals the effectiveness and relevance of using YouTube in EFL classrooms, empowering both teachers and learners with easily accessible resources that boost language skills while fostering a more engaging learning environment.